Recent Progress in Discovering the Role of Carotenoids and Their Metabolites in Prostatic Physiology and Pathology with a Focus on Prostate Cancer-A Review-Part I: Molecular Mechanisms of Carotenoid Action - Joanna Dulińska-Litewka; Yoav Sharoni; Przemysław Hałubiec; Agnieszka Łazarczyk; Oskar Szafrański; James A. McCubrey; Bartosz Gąsiorkiewicz; Piotr Laidler; Torsten Bohn (MDPI AG, 2021)
Among the vast variety of plant-derived phytochemicals, the group of carotenoids has continuously been investigated in order to optimize their potential application in the area of dietary intervention and medicine. One organ which has been especially targeted in many of these studies and clinical trials is the human prostate. Without doubt, carotenoids (and their endogenous derivatives-retinoids and other apo-carotenoids) are involved in intra- and intercellular signaling, cell growth and differentiation of prostate tissue. Due to the accumulation of new data on the role of different carotenoids such as lycopene (LC) and β-carotene (BC) in prostatic physiology and pathology, the present review aims to cover the past ten years of research in this area. Data from experimental studies are presented in the first part of the review, while epidemiological studies are disclosed and discussed in the second part. The objective of this compilation is to emphasize the present state of knowledge regarding the most potent molecular targets of carotenoids and their main metabolites, as well as to propose promising carotenoid agents for the prevention and treatment of prostatic diseases.